ANALISIS STRATEGI BERSAING BISNIS MOBILE BROADBAND - Darwin Raja Unggul (Panorama Nusantara, 2018)
Technological evolution has proven to lead a single cycle of the mobile telecommunications industry. This has shifted too, from voice to data. Data communication trends have led to mobile broadband being a highly competitive business with the emergence of smarphone with many matches and social media applications. This study aims to analyze and find competitive strategies with descriptive and so-called SWOT analysis. The results of this study indicate that mobile broadband business has been forced to cope with the growth of smart phones with various bundling products. This strategy can be applied with fit and competitve fit tests. The second strategy is to improve customer perceptions of existing internet base products to mobile broadband data in many provincial capitals such as Jakarta, Bandung, Surabaya, Semarang and Medan.